Study on Primary Angiitis of Central Nervous System - Radhakrishna Hari; Bimal Prasad Padhy (New Frontiers in Medicine and Medical Research Vol. 3, 2021)
Objective: To study the clinical features of primary central nervous system angiitis (PACNS) with case illustration and to review the current literature. Background: Primary angiitis is a rare disorder and is difficult to diagnose and there are many mimickers. Case Details: A 45year old female patient presented with headache, slurred speech and bilateral pyramidal signs on examination. There were lesions in the cranial imaging bilaterally with minimal enhancement. Based on the radiologist opinion, she was put on antitubercular treatment along with steroids by which there was substantial recovery. As the steroids were tapered five months later, there was recurrence of symptoms in the form of slurred speech and seizures. Repeated brain imaging showed recurrence of the lesions in the same areas. An open brain biopsy was suggestive of vasculitic pathology with transmural inflammation of the vessels and fibrinoid necrosis at a few places. A thorough work up for systemic vasculitic disorders was negative. Immunosuppression was initiated with corticosteroids and cyclophosphamide was instituted. There was good improvement in the follow up of two years. This study aims to review the current literature on diagnosis and treatment options of this enigmatic illness.